The burden of substance use and (mental) distress among asylum seekers: a cross sectional study - Solfrank, Maximilian; Nikendei, Christoph; Zehetmair, Catharina; Friederich, Hans-Christoph; Nagy, Ede (Frontiers in Psychiatry, 2023)
Background Asylum seekers are a particularly vulnerable population due to a wide range of external stressors. Traumatic events and difficult social/economic prospects can lead to an elevated susceptibility for substance use disorders. The aim of the present study was to determine whether asylum seekers suffering from mental or physical distress present higher levels of substance use disorder (SUD) in a state reception center in Germany and whether there are identifiable risk or protective factors. Methods We performed a hierarchical logistic regression on data of N = 238 people who had applied for asylum in Germany to analyze the SUD variance explanation by (1) sociodemographic, (2) flight-specific, and (3) psychometric (ERQ, SOC-9 L, SCL-K9) variables. On level (4), we included the location of data collection (walk-in clinic or accommodation,) as an indicator of individual’s need for a psychologist’s or General practitioner’s help in order to assess for the participant’s (mental) distress. Results Low educational level, lower sense of coherence, and mental distress (location of data collection in the psychosocial or general medical outpatient clinic) were associated with SUD. Those suffering from SUD seemed to be less aware of external stressors as SUD was also associated with low levels of reported post-migratory stress. Discussion The association of SUD with psychological distress and lower education reaffirms the concept that some vulnerable groups are at a higher risk for substance-related difficulties. Strengthening the sense of coherence with targeted interventions might enable at-risk groups to cope better with forthcoming burdens and help with abstaining from current or future consumption.